Pengaruh Self-efficacy, Perencanaan Karir, dan Teman Sebaya terhadap Minat Melanjutkan Pendidikan ke Perguruan Tinggi - Dzidni, Dzilma Arij; Santoso, Jarot tri Bowo (Paedagogie, 2026)
This research to analyze Influence of Self-Efficacy, Career Planning, and Peers on Interest in Continuing Education to University. A quantitative approach employing explanatory research design was applied. Data were collected using questionnaires with Likert scales. Participants comprised 180 students. Partial tests revealed self-efficacy, career planning, and peers each exerted positive and significant influences on interest in continuing to University. Simultaneous testing produced F value of 36.801 with significance level of 0.000, indicating all three independent variables collectively exerted significant influence on interest in continuing education to University. R² value of 0.785 demonstrated 78.5% of variance in interest in continuing education to University was explained by these three variables, while remaining 21.5% was attributable to other factors. Findings suggest integrated enhancement of psychological factors, career planning, and social environment support is required to develop student interest in pursuing University.